Targeted modifications of citrus pectin to improve interfacial properties and the impact on emulsion stability. (November 2022) - Humerez-Flores, Jessika N.; Verkempinck, Sarah H.E.; Van Loey, Ann M.; Moldenaers, Paula; Hendrickx, Marc E.
Abstract: In the present work, three specific low weight average molecular weight (Mw ) demethoxylated citrus pectin derived compounds (oligosaccharides) (CP25 kDa, CP3 kDa and CP3.8 kDa ) were generated by means of enzymatic degradation and subsequent chemical demethylesterification of three starting pectin materials (CP74144 kDa, CP53151 kDa and CP38116 kDa, respectively). These pectin oligosaccharides were structurally characterized, evaluated for their physicochemical properties, and their emulsifying and emulsion stabilizing (EF ES ) potential. In terms of structure, significant differences in Mw, degree of methylesterification (DM), monosaccharide and protein contents were observed between the initial and the generated pectin-derived samples. Interestingly, upon evaluation of the physicochemical properties of the generated pectin-derived materials, it was observed they exhibited considerably improved interfacial tension properties in comparison to the initial pectin samples. Furthermore, all pectin materials were negatively charged to similar extents. On the negative side, the low viscosity of the generated pectin compounds was observed to significantly hinder their EF ES properties. Upon refrigerated storage of the pectin emulsions, it was observed that the initial pectin materials (at pH 2.5) exhibited better EF ES potential in comparison to the generated pectin materials, despite the superior interfacial potential of the latter samples. This was mainly ascribed to the higher viscosity of the non-degraded pectin samples, in turn attributed to their larger Mw . Overall, the results obtained indicated that the Mw and DM of the polymer played an important role in the interfacial tension properties of pectin. However, viscosity of the continuous phase of the dispersion is a critical factor in the EF ES potential of pectin. Graphical abstract: Image 1 Highlights: All modified citrus pectin samples (Mw <25 kDa) evaluated exhibited enhanced surface activity. Coalescence and flocculation were considered the main destabilizing mechanisms in the emulsions formulated with low Mw (<25 kDa) pectins. Differences in viscosity increasing capacity, among the mother and modified pectin samples, are suggested to be the main factor influencing the stability of the formulated emulsions.